Excessive Daytime Sleepiness among Hypertensive US-Born Blacks and Foreign-Born Blacks: Analysis of the CAATCH Data - N. Williams; O. Abo Al Haija; A. Workneh; D. Sarpong; E. Keku; G. Ogedegbe; S. I. McFarlane; G. Jean-Louis (International Journal of Hypertension)
Background. Evidence shows that blacks exhibit greater daytime sleepiness compared with whites, based on the Epworth Sleepiness Scale. In addition, sleep complaints might differ based on individuals’ country of origin. However, it is not clear whether individuals’ country of origin has any influence on excessive daytime sleepiness (EDS). Study Objectives. We tested the hypothesis that US-born blacks would show a greater level of EDS compared with foreign-born blacks. The potential effects of sociodemographic and medical risk were also determined. Design. We used the Counseling African-Americans to Control Hypertension (CAATCH) data. CAATCH is a group randomized clinical trial that was conducted among 30 community healthcare centers in New York, yielding baseline data for 1,058 hypertensive black patients. Results. Results of univariate logistic regression analysis indicated that US-born blacks were nearly twice as likely as their foreign-born black counterparts to exhibit EDS (OR=1.87, 95% CI: 1.30–2.68, P<0.001). After adjusting for effects of age, sex, education, employment, body mass index, alcohol consumption, and smoking habit, US-born blacks were 69% more likely than their counterparts to exhibit EDS (OR=1.69, 95% CI: 1.11–2.57, P<0.01). Conclusion. Findings demonstrate the importance of considering individuals’ country of origin, in addition to their race and ethnicity, when analyzing epidemiologic sleep data.